IBM Cognos 8 Business Intelligence : the official guide - Volitich, Dan (McGraw Hill professional., 2008)
"This book shows you how to take full advantage of the robust service-oriented architecture and simplified role-based user interfaces. Learn how to create, share, and analyze data-rich reports that lead to increased productivity and better business decisions. This is a must-have guide for users of all levels, from administration to end users."--Jacket